Framing Environmental Discourse in Seba Baduy 2024 News on the BantenNews.co.id Portal - Afdi Maulfianti; Agung Gunawan Sutrisna (MID Publisher International, 2023)
Online media play an important role in shaping public perceptions of environmental issues through news construction. This study aims to analyze the framing of environmental discourse in the news coverage of Seba Baduy 2024 on BantenNews.co.id. The research employed a qualitative approach using Zhongdang Pan and Gerald M. Kosicki’s framing analysis method. Data were collected through documentation of news articles related to Seba Baduy 2024 published by BantenNews.co.id. The findings reveal that BantenNews.co.id framed Seba Baduy as a symbol of environmental preservation and the local wisdom of the Baduy community in maintaining ecological balance. This framing is reflected in the selection of headlines, diction, and news narratives emphasizing environmental conservation. The study shows that online media functions not only as a source of information but also as a medium for building public environmental awareness.